INFALLIBLE MEASURES OF REGIONAL PEOPLE'S REPRESENTATIVE COUNCIL PERFORMANCE IN FUNCTION PANGKAJENE AND ISLANDS DISTRICT BUDGETING - Rais, Rahmi; Ismail, Andi Muhammad Ishak (Meraja journal, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal